2016
DOI: 10.1371/journal.pone.0151909
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Genetic Deafness Microarray for Detecting Mutations in the Deaf in China

Abstract: ObjectiveThe aim of this study was to evaluate the GoldenGate microarray as a diagnostic tool and to elucidate the contribution of the genes on this array to the development of both nonsyndromic and syndromic sensorineural hearing loss in China.MethodsWe developed a microarray to detect 240 mutations underlying syndromic and nonsyndromic sensorineural hearing loss. The microarray was then used for analysis of 382 patients with nonsyndromic sensorineural hearing loss (including 15 patients with enlarged vestibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The hearing of some patients may improve, while others' hearing loss may remain stable for a long time or even worsen. Among the very limited reports involving the follow-up characteristics of AN patients, the hearing outcomes in a long-term follow-up remain elusive [ 43 ]. Not surprisingly, we found, in the 50 AIFM1 -positive cases, that the low frequency spectra were mostly affected, especially in the 0.25-1 kHz range.…”
Section: Discussionmentioning
confidence: 99%
“…The hearing of some patients may improve, while others' hearing loss may remain stable for a long time or even worsen. Among the very limited reports involving the follow-up characteristics of AN patients, the hearing outcomes in a long-term follow-up remain elusive [ 43 ]. Not surprisingly, we found, in the 50 AIFM1 -positive cases, that the low frequency spectra were mostly affected, especially in the 0.25-1 kHz range.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that almost 80% of NSHL cases involve autosomal-recessive inheritance with high genetic heterogeneity (Angeli et al, 2012). The major symptom of autosomal-recessive NSHL (ARNSHL) is bilaterally symmetric, severe-to-profound, and prelingual sensorineural HL, which is known to be caused mainly by monogenic mutations (Wu et al, 2016; Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A recently developed genome-wide association approach to detect loci affecting PDS susceptibility used 597 genotyped sows with 62,163 single nucleotide polymorphisms (SNPs) [11]. We developed a microarray to detect 240 variants underlying syndromic and nonsyndromic sensorineural hearing loss, including 11 distinct variants in SLC26A4 [12]. However, all of these EVA genetic diagnosis strategies rely upon either full gene sequencing or test for common variants in only the SLC26A4 gene.…”
Section: Introductionmentioning
confidence: 99%